2016
DOI: 10.1021/acsnano.6b02879
|View full text |Cite
|
Sign up to set email alerts
|

Atomically Thin Ohmic Edge Contacts Between Two-Dimensional Materials

Abstract: With the decrease of the dimensions of electronic devices, the role played by electrical contacts is ever increasing, eventually coming to dominate the overall device volume and total resistance. This is especially problematic for monolayers of semiconducting transition metal dichalcogenides (TMDs), which are promising candidates for atomically thin electronics. Ideal electrical contacts to them would require the use of similarly thin electrode materials while maintaining low contact resistances. Here we repor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
198
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(214 citation statements)
references
References 42 publications
16
198
0
Order By: Relevance
“…This configuration leads to the high electronic performance of graphene, including a room‐temperature mobility up to 140 000 cm 2 V −1 s −1 , comparable to the theoretical phonon‐scattering limit, and low‐temperature ballistic transport over 15 µm distances. Guimarães et al developed an in situ heterostructure growth method to realize a lateral MoS 2 /graphene contact, which brings about a low average contact resistance of 30 kΩ µm.…”
Section: Tuning the Device Performancementioning
confidence: 99%
“…This configuration leads to the high electronic performance of graphene, including a room‐temperature mobility up to 140 000 cm 2 V −1 s −1 , comparable to the theoretical phonon‐scattering limit, and low‐temperature ballistic transport over 15 µm distances. Guimarães et al developed an in situ heterostructure growth method to realize a lateral MoS 2 /graphene contact, which brings about a low average contact resistance of 30 kΩ µm.…”
Section: Tuning the Device Performancementioning
confidence: 99%
“…Examples include in-plane stitching of (i) one-atom-thick sheets, like graphene/hexagonal boron nitride (h-BN), 15,16 (ii) different TMDC systems or phases, [17][18][19][20][21] like MoSe 2 /WSe 2 or 1T/2H phase boundaries of MoS 2 , and (iii) one-atom-thick sheet and TMDC, like graphene/MoS 2 . [22][23][24][25] These systems provide a promising platform for realizing low-resistance contacts between 2D metals and 2D semiconductors, 5,11,21 that can be assembled into field-effect transistors (FETs) with remarkable performance. [20][21][22][23][24] To improve the device performance of 2D MSJ, a better fundamental un-derstanding of its electronic properties and operating mechanism is needed.…”
mentioning
confidence: 99%
“…[22][23][24][25] These systems provide a promising platform for realizing low-resistance contacts between 2D metals and 2D semiconductors, 5,11,21 that can be assembled into field-effect transistors (FETs) with remarkable performance. [20][21][22][23][24] To improve the device performance of 2D MSJ, a better fundamental un-derstanding of its electronic properties and operating mechanism is needed. Recently, Yu et al reported a model study based on semiclassical macroscopic theory, 26 that suggests a highly nonlocalized charge transfer and strong reduction of FL pinning in 2D MSJs.…”
mentioning
confidence: 99%
“…Extensive process calibration was required to avoid leaving oxide residues or damaging the graphene. Although we note that complete etching of the graphene might be beneficial in the contact area to lower contact resistance by producing edge contacts (side contact instead of top contact) [63][64][65].…”
Section: Discussionmentioning
confidence: 93%